ANALISIS YURIDIS PERSETUJUAN TINDAKAN MEDIK DI UNIT PELAKSANA TEKNIS PUSKESMAS MANIS JAYA KOTA TANGERANG - Erwin Januar Roman Damew; Ferry Anka Sugandar (Program Studi Hukum Universitas Pamulang, 2020)
Consent given by a patient (or close family or guardian) who has previously been given sufficient information about the plan of action and the risks to the action, which is conveyed by the doctor and / or other health care worker in a way that is understandable to the patient according to the level of education . However, in practice, there are health services ranging from health clinics, health centers to hospitals that have their own variations on the consent form or informed consent form. This requires specifically discussing informed consent from the aspect of civil law so that it can examine the issues of the juridical aspects of medical action approval (informed consent) appropriately in the responsibility of implementing medical practice. So that there is legal power and material substance of the informed consent used.